2019
DOI: 10.1111/jocd.12878
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of microneedling with topical vitamin C in the treatment of melasma

Abstract: Summary Background Despite the wide therapeutic options available for the treatment of melasma, including many active topical medications, technologies with lights and peelings, clinical control of this disorder is extremely challenging. Objectives To evaluate the effect of microneedling with topical vitamin C in the treatment of melasma. Methods Thirty female patients with melasma received six sessions of microneedling with addition of topical vitamin C every two weeks. At each session, photos were taken and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 31 publications
3
24
0
4
Order By: Relevance
“…Acknowledging that hypersensitivity and foreign‐body reactions may occur with laser‐assisted or microneedling‐assisted delivery of ascorbic acid, 14 research studies have been conducted to determine if coupling these modalities is effective 24,25 . A clinical trial coupled microneedling with 20% ascorbic acid for melasma treatment and found a 12.3% improvement in Melasma Area and Severity Index (MASI) score at 8 weeks 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acknowledging that hypersensitivity and foreign‐body reactions may occur with laser‐assisted or microneedling‐assisted delivery of ascorbic acid, 14 research studies have been conducted to determine if coupling these modalities is effective 24,25 . A clinical trial coupled microneedling with 20% ascorbic acid for melasma treatment and found a 12.3% improvement in Melasma Area and Severity Index (MASI) score at 8 weeks 24 .…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial coupled microneedling with 20% ascorbic acid for melasma treatment and found a 12.3% improvement in Melasma Area and Severity Index (MASI) score at 8 weeks 24 . In addition, another clinical trial evaluated the effect of microneedling with topical 20% L‐ascorbic acid every 2 weeks for 3 months and found a 37% improvement in MASI score 25 . However, as with treating any patient, one has to consider all variables—risks, benefits and possible side effects—and given the higher risk of local cutaneous as well as systemic reactions to transdermal drug delivery of ascorbic acid, laser‐assisted or microneedling‐assisted delivery of this compound should be approached very judiciously if at all.…”
Section: Discussionmentioning
confidence: 99%
“…The TA liposomal formulation was found to be effective because of its enhanced drug delivery, improved moisturizing effect with longer action, and controlled tissue drug distribution 21,22 . Microneedling could enhance the delivery of TA with relatively intact epidermis and limited adverse effects 23 . Furthermore, the procedure of microneedling could solely improve melasma by stimulating the proliferation of fibroblasts, the release of growth factors, and the upper dermal collagen formation 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…with topical vitamin C to be a significantly effective and safe treatment, particularly for those of Fitzpatrick skin types I-III. 17 In a separate study, patients were treated with full-face iontophoresis mask and vitamin C (ascorbyl glucoside) preparation. 18 Patients had one treatment and 12 to 24 home treatments over 1 to 2 months with sun avoidance advised.…”
Section: Vitamin Cmentioning
confidence: 99%
“…Another study of 30 patients found microneedling (six sessions) with topical vitamin C to be a significantly effective and safe treatment, particularly for those of Fitzpatrick skin types I‐III 17 …”
Section: Vitamin Cmentioning
confidence: 99%